ECONOMIC PROMOTION OF A SMALL COUNTRY – THE CASE OF SLOVENIA - Dejan ROMIH; Urban ŠEBJAN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This paper examines the economic promotion of a small country in the case of Slovenia, which is facing certain economic and social problems. One reason for this is the current financial and economic crisis, which is continuing to affect the country’s economy. Economic promotion is therefore very important for Slovenia and its economic performance in both the short and long run.